2005
DOI: 10.1002/hup.687
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine on prospective duration judgements of various intervals depend on task difficulty

Abstract: The effects of caffeine on prospective duration judgements were investigated in two double-blind placebo-controlled experiments. After taking either 200 mg of caffeine or a placebo, participants performed a task that demanded considerable attention, driving a car in a simulator (Experiment 1) or a task that demanded relatively little attention, watching a videotaped scene from a driven car (Experiment 2). Each participant made duration judgements of three target intervals: 15 s, 60 s and 300 s. Actively drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…A number of studies have shown that when arousal level is increased, participants are prone to underestimating time intervals, which has been attributed to an increase in pacemaker pulse rate (Gruber and Block 2005;Meck 1996;Penton-Voak et al 1996). In addition, distortions in time have also been reported due to attentional shifts by a distractor or unexpected event that changes the rate of information processing and thus the perception of elapsed time (Eagleman et al 2005;Tse et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that when arousal level is increased, participants are prone to underestimating time intervals, which has been attributed to an increase in pacemaker pulse rate (Gruber and Block 2005;Meck 1996;Penton-Voak et al 1996). In addition, distortions in time have also been reported due to attentional shifts by a distractor or unexpected event that changes the rate of information processing and thus the perception of elapsed time (Eagleman et al 2005;Tse et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There are several non-exclusive explanations of this effect. Possibly, caffeine is able to facilitate attention allocation that is necessary to locate a target [49]. On the other hand, caffeine could facilitate the decision making stage of visual search, which allowed BT participants to perform faster [20,50].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the caffeine condition the RT showed a stronger relationship with the alpha1 amplitude than with target probability. One possible explanation may be that caffeine has a general positive effect on general attentional resource allocation independently of the relative target probability 56 .…”
Section: Discussionmentioning
confidence: 99%